Experimental studies of electron-phonon interactions in gallium nitride - Stanton, Nicola Marie (2001)
This thesis presents an experimental investigation of the electron-phonon interaction in GaN. Bulk epilayers, grown by MBE, and AIGaN/GaN heterostructures, grown by MOCVD, have been studied. The energy relaxation rate for hot electrons has been measured over a wide range of temperatures, allowing both acoustic and optic phonon emission to be studied in GaN epilayers. Direct phonon measurements, both studying the emission and absorption processes, have been performed. Detection of phonons emitted when hot electrons relax their excess energy complements the measurements of relaxation rates. Absorption of acoustic phonons by the epilayers, using both fixed and extended metal film phonon sources, allowed investigation into the effectiveness of the 2kF cutoff in the low mobility layers. The experimental findings are compared with the predictions of theory. AIGaN/GaN heterostructures were characterised and measurements of the energy relaxation rate in the temperature range 4K-40K obtained. Excellent agreement with theory is observed. A preliminary study of phonon absorption by the 2DEG system is presented, which allowed experimental determination of the "thickness" of the 2DEG and demonstrated the applicability of the technique in the study of low dimensional systems.